Unravelling var complexity: Relationship between DBLα types and var genes in Plasmodium falciparum - Tan, Mun Hua; Shim, Heejung; Chan, Yao-ban; Day, Karen P. (Frontiers in Parasitology, 2023)
The enormous diversity and complexity of var genes that diversify rapidly by recombination has led to the exclusion of assembly of these genes from major genome initiatives (e.g., Pf6). A scalable solution in epidemiological surveillance of var genes is to use a small conserved ‘tag’ region encoding the immunogenic DBLα domain as a marker to estimate var diversity. However, the relationship between these DBLα tags and var genes has not been investigated. Analyses of in vitro recombination within and between var genes have suggested that this relationship would not be exclusive. Using a dataset of publicly-available assembled var sequences, we test this hypothesis by studying DBLα-var relationships for four study sites in four countries: Pursat (Cambodia) and Mae Sot (Thailand), representing low malaria transmission, and Navrongo (Ghana) and Chikwawa (Malawi), representing high malaria transmission. In all study sites, DBLα-var relationships were shown to be predominantly 1-to-1, followed by a second largest proportion of 1-to-2 DBLα-var relationships. This finding indicates that DBLα tags can be used to estimate not just DBLα diversity but var gene diversity when applied in a local endemic area. Epidemiological applications of this result are discussed.